Analisis Perhitungan Harga Pokok Produksi dengan Penerapan Metode Full Costing pada Produk UMKM “Pecel Kak” - M. Afrizal Miradji; Aulia Rahmayanti; Erna Nur Yuli Ana; Gresya Puspita Dewi; Indah Fitriana Putri; Meita Ais Vikadanty; Rizka Anggrainy; Yunia Salasa Tri Indah Rahmawati (Universitas Katolik Widya Karya Malang, 2023)
The calculation and recovery of production costs is greatlypinfluenced by the application of the method. As a result, production costs will show the actual value. This research was conducted at MSMEs in Sidoarjo, especially those engaged in pecel seasoning processing. This study aims to analyze the method of determining the cost of goods sold and cost allocation applied by MSMEs in Sidoarjo by calculating production costs according to the full costingrmethod. The type of4data used is qualitativeydata presented in descriptive or description form and quantitativerdata presented in numerical form. The source of data is primarysdata obtained from interviewszconducted with pecel seasoning business managers in Sidoarjo and secondary data derived from literaturepstudies and other publications that support the writing of this research. The results explain that the full costing method is suitable for analyzing production costs because it includes all general costs, fixed costs, and variable costs in the production9process.